URBAN PLANNING ASPECTS OF HUMANIZATION OF THE CITIES IMPROVEMENT: SCIENTIFIC AND PRACTICE EXPERIENCE - Dreval, Iryna (European Science, 2024)
The article is devoted to the current problem of humanization of the urban environment - a global positive process in modern architecture. Against the background of rethinking the role and place of man in the modern world, changes are taking place in the